¿Cuestión de método? sobre los cursos remediales universitarios de expresión escrita - Sánchez Avendaño, Carlos (2012)
In this article, an analysis of the results accomplished in two university courses of written communication is carried out. Both courses where conceived with different methodologies and notions of language: (1) a grammatical and prescriptive approach and (2) an approach designed to develop strategies of text production. Then, a reflection on the nature of written communication courses at the university level is presented. Finally, some objectives for such courses are outlined.